2007
DOI: 10.1897/06-303r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term sediment bioassay of lead toxicity in two generations of the marine amphipod Elasmopus laevis, S.I. Smith, 1873

Abstract: Abstract-Sediments are evaluated for toxicity by measuring mortality in a single cohort of amphipods in either acute (10-d) or chronic (28-d) bioassays. This investigation differed from conventional bioassays in four ways: Sublethal effects (fecundity) were estimated; the testing period was 60ϩ d; two successive generations were examined; and Elasmopus laevis Smith, 1873, amphipods were employed. Four test sediments were created between 58 and 424 g/g of lead using the 30-g/g whole-sediment as the control. Bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 57 publications
2
8
0
Order By: Relevance
“…In this sense, comparing the values calculated here with available ecotoxicological data (NOEC/EC 10 ) on spiked-sediment test, the Basque Country SQG values are within the range of those calculated for marine amphipods by Ringenary et al [73] for Pb, Ciarelli et al [74] for Cd, Roman et al [75] for Cu and Hagopian-Schlekat et al [65] for Ni.…”
Section: Comparison With Background Values and Other Guidelinessupporting
confidence: 85%
“…In this sense, comparing the values calculated here with available ecotoxicological data (NOEC/EC 10 ) on spiked-sediment test, the Basque Country SQG values are within the range of those calculated for marine amphipods by Ringenary et al [73] for Pb, Ciarelli et al [74] for Cd, Roman et al [75] for Cu and Hagopian-Schlekat et al [65] for Ni.…”
Section: Comparison With Background Values and Other Guidelinessupporting
confidence: 85%
“…Gale et al [6] concluded that exposure of juvenile M. plumulosa over a six-week life-cycle test to a field-collected sediment contaminated with Zn, Pb, and Cd resulted in lower numbers of juveniles in the first brood after they reached sexual maturity. More recently, Ringenary et al [23] demonstrated a dose-dependant relationship between the numbers of offspring of the amphipod Elasmopus laevis recovered from sediments at the termination of nine-week chronic exposures to Pb-spiked sediments (five concentrations between 30 and 424 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…Any disruption of the synchronism of these endpoints by a chemical contaminant would highlight a possible endocrine disruption mechanism. In general, available methodologies for an amphipod reproductive toxicity test cannot discriminate or assess whether the reproductive impairment observed results from a decrease in the number of oocytes produced, an impact on the fertility related to embryonic impairment, or a delay in organism growth [4,5,50].…”
Section: Reproductive Toxicity Test Inmentioning
confidence: 99%